Efficacy of Shenqi Pollen Capsules for High-Altitude Deacclimatization Syndrome via Suppression of the Reoxygenation Injury and Inflammatory Response - Binfeng He; Mingdong Hu; Zhihui Liang; Qianli Ma; Yunhai Zi; Zhiwei Dong; Qi Li; Yongjun Luo; Guisheng Qian; Liang Guo; Kexiong Lin; Zhenyu Liu; et al. (Journal of Immunology Research)
High-altitude deacclimatization syndrome (HADAS) is involved in hypoxia-reoxygenation injury and inflammatory response, induced a series of symptoms, and has emerged as a severe public health issue. Here, we investigated the mechanism as well as potential means to prevent HADAS using Shenqi pollen capsules (SPCs) in subjects with HADAS in a multicenter, double-blinded, randomized, placebo-controlled study. All subjects were at the same high altitude (3650 m) for 4-8 months before returning to lower altitudes. Subjects (n=288) in 20 clusters were diagnosed with mild or moderate HADAS on the third day of the study. We randomly allocated 20 clusters of subjects (1 : 1) to receive SPCs or a placebo for 7 weeks, and they were then followed up to the 14th week. The primary endpoints were subjects’ HADAS scores recorded during the 14 weeks of follow-up. Compared with the placebo, SPC treatment significantly decreased the subjects’ HADAS scores and reduced the incidence of symptom persistence. SPC therapy also reduced the serum levels of CK, CK-MB, LDH, IL-17A, TNF-α, and miR-155 and elevated IL-10 and miR-21 levels. We thus demonstrate that SPCs effectively ameliorated HADAS symptoms in these subjects via suppression of the hypoxia-reoxygenation injury and inflammatory response.